Usability analysis taking into consideration the aspects of accessibility of selected university websites - Kałan, Karol; Karpiuk, Damian; Dzieńkowski, Mariusz (Journal of Computer Sciences Institute, 2021)
The goal of this paper was to evaluate selected web services of universities in terms of user experience, with particular emphasis on usability and accessibility. The research was conducted using eye-tracking and questionnaire methods. Ten people participated in this study. The objects of the study were three university websites: the Catholic University of Lublin (KUL), the Cracow University of Technology (PK) and the West Pomeranian University of Technology (ZUT). The eye-tracking data were subjected to qualitative and quantitative analyses, while the data from questionnaires were subjected to quantitative analysis. The results of individual analyses are presented in the form of heat maps, scan paths, charts and tables.